Health care utilization and end‐of‐life care for older patients with acute myeloid leukemia. Issue 16 (29th April 2015) - El‐Jawahri, Areej R.; Abel, Gregory A.; Steensma, David P.; LeBlanc, Thomas W.; Fathi, Amir T.; Graubert, Timothy A.; DeAngelo, Daniel J.; Wadleigh, Martha; Ballen, Karen K.; Foster, Julia E.; Attar, Eyal C.; Amrein, Philip C.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Health care utilization in older adults (age ≥60 years) with acute myeloid leukemia (AML) has not been well studied. METHODS We conducted a retrospective analysis of 330 consecutive older patients who were diagnosed with AML between May 1, 2005 and December 23, 2011, at 2 hospitals in Boston to examine their health care utilization and end‐of‐life care. Using multivariable logistic and linear regression models adjusting for covariates, we also compared health care utilization between patients who received intensive induction chemotherapy (n = 197; cytarabine/ anthracycline combination) versus nonintensive chemotherapy (n = 133; single‐agent therapy). RESULTS The median number of hospitalizations for the entire cohort was 4.2 (range, 1‐18 hospitalizations). Patients who died spent a mean of 28.3% of their life after diagnosis in the hospital and 13.8% of their life attending outpatient clinic appointments. Although the majority of patients (87.9%) died during the 2‐year follow‐up period, a minority received palliative care (16.2%) or hospice (23.1%) services. Within 30 days of death, 84.5% of patients were hospitalized, and 61% died in the hospital. Among the patients who died, those who received intensive induction therapy (vs nonintensive therapy) spent 30% more of their life after diagnosis in the hospital (P < .0001) and were less likely to receive hospice services (odds ratio, 0.45; P = .05). CONCLUSIONS The current findings highlight the intensity of health care utilization among older patients with AML, regardless of treatment modality. Despite the poor prognosis, palliative care and hospice services are rarely used. Future work should study novel health care delivery models to optimize care throughout the course of illness and at the end of life. Cancer 2015;121:2840‐2848. © 2015 American Cancer Society